Measurements of Ultra Wide Band In-vehicle channel - statistical description and TOA positioning feasibility study - Blumenstein, Jiří; Prokeš, Aleš; Mikulášek, Tomáš; Maršálek, Roman; Zemen, Thomas; Mecklenbräuker, Christoph (Springer, 2015)
This paper reports on a real-world wireless channel measurement campaign for in-vehicle scenarios in the ultra wide bandwidth (UWB) frequency range of 3-11 GHz. The effects of antenna placement in the vehicle's passenger compartment, as well as the effects due to the presence of passengers are studied. The measurements have been carried out in the frequency domain and the corresponding channel impulse responses (CIRs) have been estimated by inverse Fourier transform. The inuence of a specifc band group selection within the whole UWB range is also given. Statistical analysis of the measured channel transfer functions gives a description of the wireless channel statistics in the form of a generalized extreme value process. The corresponding parameter sets are estimated and documented for all permutations of antenna placement and occupancy patterns inside the vehicle's passenger compartment. Further, we have carried out a feasibility study of an in-vehicle UWB based localization system based on the time of arrival (TOA)). The positioning performance is evaluated in terms of average error and standard deviation.

This paper reports on a real-world wireless channel measurement campaign for in-vehicle scenarios in the ultra wide bandwidth (UWB) frequency range of 3-11 GHz. The effects of antenna placement in the vehicle's passenger compartment, as well as the effects due to the presence of passengers are studied. The measurements have been carried out in the frequency domain and the corresponding channel impulse responses (CIRs) have been estimated by inverse Fourier transform. The inuence of a specifc band group selection within the whole UWB range is also given. Statistical analysis of the measured channel transfer functions gives a description of the wireless channel statistics in the form of a generalized extreme value process. The corresponding parameter sets are estimated and documented for all permutations of antenna placement and occupancy patterns inside the vehicle's passenger compartment. Further, we have carried out a feasibility study of an in-vehicle UWB based localization system based on the time of arrival (TOA)). The positioning performance is evaluated in terms of average error and standard deviation.
Measurements of Ultra Wide Band In-vehicle channel - statistical description and TOA positioning feasibility study
Keywords: UWB; in-vehicle environment; channel model; positioning; TOA; UWB; in-vehicle environment; channel model; positioning; TOA